PENGARUH PENYIMPANGAN KETEBALAN DAN MUTU PELAT BETON PADA PERKERASAN BETON SEMEN (PERKERASAN KAKU) - Furqon Affandi (Jurnal Jalan-Jembatan, 2004)
The application of concrete pavement in Indonesia started 1995, there was increase in its development but no significant, Rigid pavement type with commonly use in Indonesia is plain concrete pavement due to the simplicity in application and cheap, with typical slab thickness of 25 cm. The influence of the change composite reaction by approximately Â± 25% will change the service life by Â± 6%. From the analysis of slab thickness and concrete quality deficiencies, gave significant influence on pavement service life. The descrease of slab thickness by 25 mm of design thickness or the decrease of concrete quality by 20% of design quality will decrease half of pavement service life. Even though there is compensation by decreasing the payment on the contract unit price but economic analysis on disadvantages is required.